2020
DOI: 10.1371/journal.pmed.1003058
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing systemic steroids for acute respiratory tract infections in United States outpatient settings: A nationwide population-based cohort study

Abstract: Background Evidence and guidelines do not support use of systemic steroids for acute respiratory tract infections (ARTIs), but such practice appears common. We aim to quantify such use and determine its predictors. Methods and findings We conducted a cohort study based on a large United States national commercial claims database, the IBM MarketScan, to identify patients aged 18-64 years with an ARTI diagnosis (acute bronchitis, sinusitis, pharyngitis, otitis media, allergic rhinitis, influenza, pneumonia, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
0
15
0
4
Order By: Relevance
“…A distinct gender difference was found in that males had a lower RIT age-standardized incidence rate (except tuberculosis), but severer outcomes as a higher age-standardized death and DALY rate, which accorded with many previous studies concerning respiratory infection disease. 16 For instance, the ratio of male to female was 1:1.27 in a US nationwide population-based acute respiratory infection study involving 9,763,710 outpatients, 17 but the male-to-female ratio of tuberculosis was 1.88:1 in 1999. 18 Moreover, the hazard ratio of mortality for males was 1.33 in active tuberculosis 19 and 1.59 in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…A distinct gender difference was found in that males had a lower RIT age-standardized incidence rate (except tuberculosis), but severer outcomes as a higher age-standardized death and DALY rate, which accorded with many previous studies concerning respiratory infection disease. 16 For instance, the ratio of male to female was 1:1.27 in a US nationwide population-based acute respiratory infection study involving 9,763,710 outpatients, 17 but the male-to-female ratio of tuberculosis was 1.88:1 in 1999. 18 Moreover, the hazard ratio of mortality for males was 1.33 in active tuberculosis 19 and 1.59 in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Fuera de las enfermedades oncológicas, los corticoides se indican en una miríada de enfermedades agudas o crónicas, y sus efectos secundarios son proporcionales a la duración y a la dosis prescripta. 5 En pediatría es frecuente su uso fuera de las recomendaciones. En este sentido, es necesario revisar las indicaciones de uso de corticosteroides sistémicos para las infecciones respiratorias agudas (IRA) y los problemas de seguridad asociados.…”
Section: Discussionunclassified
“…Los corticoides sistémicos como tratamiento de la insuficiencia renal aguda carecen de evidencia fuerte, sin embargo, su uso continúa en aumento. 5 El tratamiento indicado en otra institución con antibióticos y corticoides por un cuadro de disnea y tos de 20 días de evolución debe llamarnos a la reflexión a los pediatras. Las IRA se encuentran entre las enfermedades agudas más comunes en pediatría.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A series of meta-analyses based on small trials with significant flaws has led to a significant increase in interest in corticosteroids in CAP, 34,35 with evidence of large scale overuse of these potentially toxic agents. 36 A more detailed discussion of the primary papers used by the meta-analyses has been published. 37 Of significance, Torres et al 38 used an entry criteria of a C-reactive protein greater than 150 mg/dL, but found no difference in mortality or length of hospital stay in 120 patients.…”
Section: Advances In Treatment: Antimicrobials For Pneumoniamentioning
confidence: 99%